2018
DOI: 10.14639/0392-100x-1342
|View full text |Cite
|
Sign up to set email alerts
|

Cyclamen europaeum improves the effect of oral antibiotics on exacerbations and recurrences of chronic rhinosinusitis: a real-life observational study (CHRONOS)

Abstract: Cyclamen europaeum improves the effect of oral antibiotics on exacerbations and recurrences of chronic rhinosinusitis: a real-life observational study (CHRONOS) L'estratto di Cyclamen europaeum per via intranasale implementa l'effetto degli antibiotici orali nel trattamento delle riacutizzazioni delle rinosinusiti croniche: studio osservazionale in vivo (CHRONOS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Among the few studies that only utilized EHR as their data source, the prospective cohort study by Lopatin et al was conducted at 16 clinical centers to evaluate the following three treatment options for chronic rhinosinusitis (CRS): oral antibiotics plus the herb Cyclamen europaeum ( CE) , CE in monotherapy, and oral antibiotics alone [ 13 ]. By analyzing multicenter EHRs, this study was able to show that CE in monotherapy or in combination with a standard oral antibiotic significantly reduced CRS symptoms and recurrences compared to oral antibiotics alone among patients with CRS exacerbation.…”
Section: Real-world Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the few studies that only utilized EHR as their data source, the prospective cohort study by Lopatin et al was conducted at 16 clinical centers to evaluate the following three treatment options for chronic rhinosinusitis (CRS): oral antibiotics plus the herb Cyclamen europaeum ( CE) , CE in monotherapy, and oral antibiotics alone [ 13 ]. By analyzing multicenter EHRs, this study was able to show that CE in monotherapy or in combination with a standard oral antibiotic significantly reduced CRS symptoms and recurrences compared to oral antibiotics alone among patients with CRS exacerbation.…”
Section: Real-world Data Sourcesmentioning
confidence: 99%
“…As EHR can obtain large datasets that include extensive laboratory data and hospital test results, it provides an additional layer of information about the patients that could potentially be impactful to the study outcome. Loptain et al demonstrated this by incorporating the nasal endoscopy test to objectively assess the study outcome in their herbal-drug research, thus reducing the possibility of outcome misclassification [ 13 ]. Coupled with the fact that EHR can also provide records on HMs that are not exclusively limited to reimbursed herbs, this data source provides a relatively complete dataset for analysis.…”
Section: Real-world Data Sourcesmentioning
confidence: 99%
“…In several studies targeting patients with TTH, the frequency of vestibular signs/symptoms was high, and abnormalities were reported in vestibular function tests [6,4]. Furthermore, in several cross-sectional studies, various types of headache were shown to be associated with tinnitus and hearing impairment, including TTH, mixed headache, and headache combined with cervical muscle tenderness [20,21,23]. In population-based cohort studies from Taiwan, a relationship was observed between primary headache mainly in patients with TTH and cochlear disorders [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…In previous population-based cohort studies, migraines were suggested to increase the risk of tinnitus, sensorineural hearing impairment, and/or sudden deafness [18,19]. In addition, the relationship between headaches and tinnitus or hearing impairment has been described in several clinical studies [20][21][22][23][24][25]. In cross-sectional studies, several types of headaches, including migraine and TTH, were shown to be associated with tinnitus and hearing impairment [23,20].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation